Gut metabolites and bacterial community networks during a pilot intervention study with flaxseeds in healthy adult men - Lagkouvardos, Ilias; Kläring, Karoline; Heinzmann, Silke S; Platz, Stefanie; Scholz, Birgit; Engel, Karl‐Heinz; Schmitt‐Kopplin, Philippe; Haller, Dirk; Rohn, Sascha; Skurk, Thomas; Clavel, Thomas (Molecular nutrition & food research, 2015)
SCOPE: Flaxseeds contain the phytoestrogens lignans that must be activated to enterolignans by intestinal bacteria. We investigated the impact of flaxseeds on fecal bacterial communities and their associations with fecal and blood metabolites. METHODS AND RESULTS: Nine healthy male adult subjects ingested 0.3 g/kg/day flaxseeds during 1 week. Gut bacteria as well as blood and fecal metabolites were analyzed. Ingestion of flaxseeds triggered a significant increase in the blood concentration of enterolignans, accompanied by fecal excretion of propionate and glycerol. Overall diversity and composition of dominant fecal bacteria remained individual specific throughout the study. Enterolactone production was linked to the abundance of two molecular species identified as Ruminococcus bromii and Ruminococcus lactaris. Most dominant species of the order Bacteroidales were positively associated with fecal concentrations of either acetic, isovaleric, or isobutyric acid, the latter being negatively correlated with blood levels of triglycerides. The relative sequence abundance of one Gemmiger species (Ruminococcaceae) and of Coprococcus comes (Lachnospiraceae) correlated positively with blood levels of LDL cholesterol and triglycerides, respectively. CONCLUSION: Flaxseeds increase enterolignan production but do not markedly alter fecal metabolome and dominant bacterial communities. The data underline the possible role of members of the family Ruminococcaceae in the regulation of enterolignan production and blood lipids.